The Analysis Of Effectiveness Of Habit Forming Method Implementation To Improve Discipline In Students Learning Activities - Adil, Ahmad; Zuraida; Fathurohman, Apit; Taobah Ramdani, Hasbi; Novaria, Novi (Mudir : Jurnal Manajemen Pendidikan, 2023)
This study aims to determine whether the habit-forming method can improve student learning discipline in thematic learning. In obtaining a research result, researchers use a mixed method that combines qualitative and quantitative methods, which are combined in a study. In this study, the qualitative method is more dominant, and the complementary method is the quantitative method. With the habit-forming method, it can influence students' learning discipline. Entering on time, doing assignments on time, and learning are stimulated to instill habituation in reciting rote memorization that has been memorized so that it is always remembered, so it is very effectively applied to students when at home during learning.